2011
DOI: 10.1371/journal.pone.0017039
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin-Mediated Proliferation and Innate Immune Activation in Celiac Disease Are Due to Alterations in Vesicular Trafficking

Abstract: Background and ObjectivesDamage to intestinal mucosa in celiac disease (CD) is mediated both by inflammation due to adaptive and innate immune responses, with IL-15 as a major mediator of the innate immune response, and by proliferation of crypt enterocytes as an early alteration of CD mucosa causing crypts hyperplasia. We have previously shown that gliadin peptide P31-43 induces proliferation of cell lines and celiac enterocytes by delaying degradation of the active epidermal growth factor receptor (EGFR) due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 39 publications
2
62
0
8
Order By: Relevance
“…This can result in target cell killing thus contributing to the disappearance of the villi in CD. Subsequent studies showed that p31-43 altered the trafficking of vesicular compartments in the intestinal Caco-2 cell line leading to overexpression of IL-15/IL5R alpha complex and delaying the degradation of the active epidermal growth factor receptor (EGFR) that induces cell proliferation of cell lines and, possibly, crypts hyperplasia in CD [35]. More recently, gliadin peptide p31-43 was reported to induce tTGase activation in Caco-2 cells, an event mediated by the release of Ca 2+ ions from intracellular stores [24].…”
Section: Discussionmentioning
confidence: 99%
“…This can result in target cell killing thus contributing to the disappearance of the villi in CD. Subsequent studies showed that p31-43 altered the trafficking of vesicular compartments in the intestinal Caco-2 cell line leading to overexpression of IL-15/IL5R alpha complex and delaying the degradation of the active epidermal growth factor receptor (EGFR) that induces cell proliferation of cell lines and, possibly, crypts hyperplasia in CD [35]. More recently, gliadin peptide p31-43 was reported to induce tTGase activation in Caco-2 cells, an event mediated by the release of Ca 2+ ions from intracellular stores [24].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to prolonged epidermal growth factor receptor inactivation, overexpression of transpresented interleukin (IL) 15/IL15 receptor-α complex as well as increased reactive oxygen species generation, and TG2 activation (16,(30)(31)(32). Such a complex cascade of intracellular events following gliadin exposure likely derails intracellular control systems thus disrupting Ca 2+ homeostasis by still unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…2). This upregulation has been attributed to a specific subset of toxic gliadin peptides which includes for instance the peptide p31-43 [139]. IL-15 induces a simultaneous upregulation of MICA expression in epithelial cells [140] and the activating NKG2D receptor in intraepithelial lymphocytes [141].…”
Section: Biology Underlying Celiac Disease Adaptive and Innate Immunementioning
confidence: 99%